No laughing, no smiling, no giggling - Stevenson, James, 1929-2017. (New York : Farrar, Straus and Giroux, 2004)
The reader joins Freddy Fafnaffer the pig as he deals with Mr. Frimdimpny, a crocodile who never laughs and who decides on the rules for reading this book.
Accelerated Reader/Renaissance Learning
A Junior Library Guild selection.
Keywords: Laughter -- Fiction; Behavior -- Fiction; Swine -- Fiction; Crocodiles -- Fiction; Laughter -- Juvenile fiction; Swine -- Juvenile fiction; Crocodiles -- Juvenile fiction